The Influence of Leadership, Communication, Personality, Motivation, and Competence on Employee Performance PT. Traya Tirta Cisadane - Dadang Rachmat; Sri Langgeng Ratnasari; Widodo Ismanto (Cita konsultindo, 2024)
Improving the quality of human resources makes performance more competitive for the sustainability of the company. The purpose of this research is to determine and analyze the influence of leadership on employee performance, communication on employee performance, personality on employee performance, motivation on employee performance, competence on employee performance and leadership, communication, personality, motivation, competence together on employee performance. The population of this research is employees of PT. Traya Tirta Cisadane, numbering 55 people. The sample consisted of 55 respondents, samples were taken using the census method. Data analysis used multiple regression and hypothesis testing using the SPSS version 25 test tool. The results of this study concluded that leadership had a positive and significant effect on employee performance, communication had a positive and significant effect on employee performance, personality had a positive and significant effect on employee performance, motivation had an effect positive and significant impact on employee performance, competency has a positive and significant impact on employee performance Leadership, communication, personality, motivation, competence together have a positive and significant impact on employee performance